Pengaruh Beban Kerja, Stres Kerja, dan Lingkungan Kerja terhadap Tingkat Turnover Intention pada PT. Sepulsa Teknologi Indonesia - Dhea Wulandari; Kardinah Indrianna Meutia; Nita Komala Dewi (Pusat Riset dan Inovasi Nasional, 2025)
This research uses a quantitative approach with a survey method involving employees of PT Sepulsa Technology Indonesia. At this start, 60 respondents were taken as samples. The study uses SmartPLS 4.0 statistics to test the hypothesis. The results of the analysis showed that the workload variable has a negative and non-significant influence on the turnover intention, the work stress has a positive and significant influence upon the turnover intentions, the working environment has a negative and insignificant effect on turnover intention, the load of work, work stres, and the work environment have a significant simultaneous influence over the turnover intention. This research has the accuracy of research objects that are carried out only by employees of PT. Sepulsa Technology Indonesia. The innovation in this research combines variables of workload, work stress, and work environment against the turnover intention of employees of PT. Sepulsa Technology Indonesia.